2008
DOI: 10.1111/j.1462-5822.2008.01186.x
|View full text |Cite
|
Sign up to set email alerts
|

Capsule enlargement inCryptococcus neoformansconfers resistance to oxidative stress suggesting a mechanism for intracellular survival

Abstract: SummaryCryptococcus neoformans is a facultative intracellular pathogen. The most distinctive feature of C. neoformans is a polysaccharide capsule that enlarges depending on environmental stimuli. The mechanism by which C. neoformans avoids killing during phagocytosis is unknown. We hypothesized that capsule growth conferred resistance to microbicidal molecules produced by the host during infection, particularly during phagocytosis. We observed that capsule enlargement conferred resistance to reactive oxygen sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
198
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 230 publications
(221 citation statements)
references
References 71 publications
9
198
1
4
Order By: Relevance
“…Another well-known example is Cryptococcus neoformans. This encapsulated yeast has developed different mechanisms to evade killing by the macrophages, including formation of leaky phagolysosomes (30) and induction of capsule enlargement, which confers protection to free radicals (33). In the case of C. krusei, we have observed that there is a defect in the maturation of the phagolysosome by using different markers of this process, such as Lamp1 and LysoTracker.…”
Section: Discussionmentioning
confidence: 88%
“…Another well-known example is Cryptococcus neoformans. This encapsulated yeast has developed different mechanisms to evade killing by the macrophages, including formation of leaky phagolysosomes (30) and induction of capsule enlargement, which confers protection to free radicals (33). In the case of C. krusei, we have observed that there is a defect in the maturation of the phagolysosome by using different markers of this process, such as Lamp1 and LysoTracker.…”
Section: Discussionmentioning
confidence: 88%
“…Gene ontology analysis of differentially expressed genes has shown that adaptation of C. neoformans to H 2 O 2 treatment is distinct from the response of other fungal organisms to oxidative stress (41). One reason for this is that C. neoformans is encapsulated and both the size and the biophysical properties of the exo-PS of C. neoformans affect its resistance to oxidative stress (13,17). Our results now demonstrate that the exo-PS of all2⌬ cells is augmented and has altered biophysical properties, namely, decreased viscosity compared to the exo-PS of the wild type.…”
Section: Discussionmentioning
confidence: 99%
“…Mutants were phenotypically characterized for (i) baseline and induced capsule size, (ii) growth rate in variable pH and Dulbecco's modified Eagle's medium (DMEM) supplemented with 10% fetal calf serum, 10% NCTC, 1% nonessential amino acids, 1% penicillinstreptomycin, or minimal medium (10 mM magnesium sulfate, 29.3 mM potassium phosphate monobasic, 13 mM glycine, 3 M thiamine-HCl; adjusted to pH 5.5 and supplemented with 15 mM glucose as the carbon source), (iii) in vitro stress sensitivity (1 M potassium chloride, lithium chloride [100 and 200 mM with glucose and galactose, respectively], 1 M sodium chloride), (iv) hydrogen peroxide sensitivity, (v) macrophage phagocytosis index, and (vi) macrophage-mediated killing assays as described previously (13)(14)(15)(16). The intrinsic viscosity of exopolysaccharide and glucuronic acid residue content was determined as previously described (17,18).…”
Section: Methodsmentioning
confidence: 99%
“…This is not necessarily surprising since C. neoformans, in contrast with Mycobacterium, does not actively prevent the acidification or maturation of the phagosome (Feldmesser et al, 2000; Levitz et al, 1999), a process that in Mycobacterium-infected AMs is indeed controlled by S1P (Garg et al, 2004;Kusner, 2005;Malik et al, 2000; Thompson et al, 2005). In addition, C. neoformans possesses virulence factors enabling internalized C. neoformans cells to survive within this microbicidal intracellular environment (Cox et al, 2001Shea et al, 2006;Wright et al, 2007;Zaragoza et al, 2008).…”
Section: Discussionmentioning
confidence: 99%